Dear Super-Villains: A Graphic Novel - Northrop, Michael; Duarte, Gustavo, 1977-; Peter, Cris; Abbott, Wes. (Burbank, CA : DC Comics, 2021)
"Peek inside the lives of DCs infamous rogues gallery, where curious kids write to notorious scoundrels, asking them about life on the dark side. Read between the lines and you may notice the baddies are up to something big. Will the Justice League show up in time to stop them?"--
"Superman created by Jerry Siegel and Joe Shuster. By special arrangement with the Jerry Siegel family."
Ages 8-12.
Grades 4-6.
Keywords: Supervillians -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Supervillians -- Fiction; Superheroes -- Fiction; Superhero comics; Comics (Graphic works)